Fibrous Dysplasia of the Ethmoid Bone Diagnosed in a 10-Year-Old Patient - Zofia Resler; Monika Morawska-Kochman; Katarzyna Resler; Tomasz Zatoński (Medicina)
Fibrous dysplasia is an uncommon bone disorder affecting various parts of the skeleton, often affecting facial and cranial bones. In this case, a 10-year-old patient was diagnosed with fibrous dysplasia of the ethmoid sinus at an early age. The patient has experienced nasal congestion, snores, and worsening nasal patency since 2019. A CT scan revealed an expansive proliferative lesion, likely from the frontal or ethmoid bone, protruding into the nasal cavity, ethmoid sinus, and right orbit. The tumor causes bone defects in the area of the nasal bone, leading to fluid retention in the peripheral parts of the right maxillary sinus. The patient’s parents decided not to undergo surgery to remove the diseased tissue and reconstruct the area, as it would be very extensive, risky, and disfiguring. The patient is being treated conservatively with an MRI, with a contrast performed approximately every six months and infusions of bisphosphonates. Despite the lesion’s size, the patient does not experience pain characteristic of dysplasia, and functions typically. Fibrous dysplasia of bone is a rare condition that presents with the most visually apparent manifestations, often mistaken for other bone conditions. Advanced diagnostic tools, like CT and MRI, are used to identify conditions affecting the ethmoid sinus more frequently. However, diagnostic errors often occur in imaging studies, leading to confusion. The most common period for clinical manifestations and diagnosis is around 10 years of age. The preferred approach in managing fibrous dysplasia involves symptomatic treatment, which can alleviate airway obstruction, restore normal globe position and visual function, and address physical deformities. Surgical intervention is recommended only for patients with severe functional impairment, progressive deformities, or malignant transformation.